A novel water‐soluble polythiophene derivatives based fluorescence "turn‐on" method for protein determination. Issue 2 (17th April 2013) - Wang, Lin; Zhang, Guangyou; Pei, Meishan; Hu, Linlin; Li, Enyong; Li, Huizhi
<x xml:space="preserve">Abstract</x> A lable‐free, simple, and sensitive fluorescence "turn‐on" approach is designed to rapidly detect protein using a conjugated polythiophene derivative (PDPMT‐Cl). The fluorescence of PDPMT‐Cl solution can be efficiently quenched by PtCl42− ions. Upon adding trypsin to the (bovine serum albumin, BSA) PDPMT‐Cl–PtCl42− solution, the BSA is cleaved into amino acid or peptide fragments, which are stronger PtCl42− ions chelators to form more stable complexes with PtCl42− ions. Thus, the PtCl42− ion is displaced from PDPMT‐Cl and the fluorescence of PDPMT‐Cl is recovered. By triggering the "turn‐on" signal of PDPMT‐Cl, it is successful to detect the protein in real time. "Turn‐on" response as readout signal is able to effectively reduce background noise and increase detection sensitivity. This method offers good selectivity for detecting protein in the presence of other common amino acids and metal ions. Under optimized conditions, the concentration of BSA in the range of 0.0004–1.75 mg/mL exhibits a linear relationship with the relative fluorescence intensity, and the correlation coefficient is 0.9997. The limit of detection is 4.47 × 10−4 mg/mL. The system is successfully applied for detecting protein in milk and egg. Due to the simplicity, sensitivity, and rapid response, this assay shows great potential for protein detection in the future. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 939‐943, 2013